'A real show for mature women' ageing along with ageing stars: Grace and Frankie fandom on Facebook. Issue 2 (3rd April 2018) - Jerslev, Anne
ABSTRACT: Based on a qualitative content analysis of two sets of comments to posts about the Netflix' series Grace and Frankie on Jane Fonda's Facebook page, the aim of this article is to discuss older women's intense appreciation of the series. Primarily on account of the comments from the older female writers in the sample (above the age of 50), the article asks in which ways are the older female characters and the series' portrayal of ageing appraised by the older female fans? The study concludes that the affective attachment to the characters and the series' universe is based on recognition and identification, at the same time as the series offers the women a humorous distance from the fact of ageing and being old. Moreover, the article concludes that commenters describe how the show adds value to their everyday lives and how they can hardly wait to binge-watch a new season. Finally, commenters' ordinary fandom is expressed through paying homage to two extraordinary older actresses whom the older fans have followed for a long time, and who are still going strong and projecting a positive image of ageing.